Procurement in the Age of Supply Chain Disruptions: Strategies for Building Resilient Networks - Balkhair, Reema Mohammed (ExcelingTech, 2025)
In today’s age of volatility, where the slightest sign of uncertainty can unravel even the most meticulously developed plans, supply chains bear the burden of navigating a storm of intensifying geopolitical tensions, pandemics, environmental disasters, and economic flux. Earlier procurement models, portrayed disruptions as insulated-in-nature, with effects being confined to a certain region or supplier. However, as supply chains become more global and turbulent, a new procurement paradigm is needed, one that prioritizes resilience. Through practical examples and insights, this paper proposes an actionable farmwork for how organizations can become proactivity equipped for modern-day risks through employing a combination of strategies such as supplier diversification, emerging digital solutions, and inventory models, all of which effectively manage risks and maintain agility. It also explores the substantial upfront investment costs and administrative complexities as main deterrents of immediate implementation. However, it goes on to demonstrate how this farmwork establishes the foundations for long-term value, in both adaptability and stability, making them ultimately worthwhile.